ANALISIS KEPATUHAN PASIEN BPJS KESEHATAN DALAM PROSEDUR PELAYANAN RUJUKAN DI RSUD ARIFIN ACHMAD PROVINSI RIAU TAHUN 2023 - Ningsih, Lestari Aulia (LPPM Universitas Awal Bros, 2025)
Referral system is the organization of health services regulate the delegation of duties and responsibilities of health services in a comprehensive manner feedback both vertically and horizontally. In the administrative service system, for handling patients, the Social Security Administering Agency itself has a certain flow which serves as a separation between the hospital's default administrative system and the Social Security Administering Agency. This research aimed to determine patient compliance with the Social Security Administering Agency for Health in the Referral Service Procedures of the Social Security Administering Agency at Arifin Achmad Hospital, Riau Province in 2023. This research used qualitative descriptive research design. This research was conducted by conducting in-depth interviews with 7 informants. This research was carried out in August-September 2023. The results of the research showed that the majority of patients or patient families had followed and complied with the flow and requirements of the Health Social Security Administering Body, but there were also those who had not complied with the flow and requirements of the Health Social Security Administering Body.For system referrals from the Social Security Administering Agency for Health run optimally in accordance with the rules of the referral system for the Social Security Administering Agency for Health and Services. Registration officers are in accordance with Standard Operating Procedures.